Can hyperoxic preconditioning in normobaric hypoxia (3500 m) improve all-out exercise performance in highly skilled skiers? A randomized crossover study - Morawetz, D.; Dünnwald, T.; Faulhaber, M.; Gatterer, H.; Höllrigl, L.; Raschner, C.; Schobersberger, W. (International Journal of Sports Physiology and Performance, 2020)
Background: The altering effects of hypoxia on aerobic/anaerobic performance are well documented and form the basis of this study. Application of hyperoxic gases (inspiratory fraction of oxygen [FiO2]>0.2095) prior to competition or training (hyperoxic preconditioning) can compensate for the negative influence of acute hypoxia. Purpose: To investigate whether oxygen supplementation immediately prior to exercise (FiO2=1.0) improves all-out exercise performance in normobaric hypoxia (3500 m) in highly skilled skiers. Methods: In this single-blind, randomized, crossover study, 17 subjects performed a 60-second constant-load, all-out test in a normobaric hypoxic chamber. After a short period of adaptation to hypoxia (60 min), they received either pure oxygen or chamber air for 5 minutes prior to the all-out test (hyperoxic preconditioning vs nonhyperoxic preconditioning). Capillary blood was collected 3 times, and muscle oxygenation was assessed with near-infrared spectroscopy. Results: Absolute and relative peak power (P=.073 vs P=.103) as well as mean power (P=.330 vs P=.569) did not significantly differ after the hyperoxic preconditioning phase. PaO2 increased from 51.3 (3) to 451.9 (89.0) mm Hg, and SaO2 increased from 88.2% (1.7%) to 100% (0.2%) and dropped to 83.8% (4.2%) after the all-out test. Deoxygenation (P=.700) and reoxygenation rates (P=.185) did not significantly differ for both preconditioned settings. Conclusions: Therefore, the authors conclude that hyperoxic preconditioning did not enhance 60-second all-out exercise performance in acute hypoxia (3500 m).